Inquisitors and heretics in thirteenth-century Languedoc : edition and translation of Toulouse inquisition depositions, 1273-1282 - Biller, Peter; Bruschi, Caterina, 1968-; Sneddon, Shelagh (Leiden ; Boston : Brill, 2011)
In the study of inquisition and heresy in Languedoc the late-13th century is a dark hole. This book redresses this, providing an edition and translation of depositions of heresy suspects interrogated in Toulouse 1273-82, preserved in a copy of 1669.
pt. 1. Introduction. The history of Doat 25-26 / Peter Biller -- The inquisition of 1273-1282 / Peter Biller -- Interrogation, notaries and witnesses / Caterina Bruschi, Shelagh Sneddon, Peter Biller -- Scribal errors and the conventions of this edition / Shelagh Sneddon, Peter Biller -- pt. 2. Edition and translation of Doat 25-26. List of deponents, in order of appearance 25-26 -- Calendar of depositions / Shelagh Sneddon -- Edition and translation / Shelagh Sneddon, Peter Biller.
English and Latin, translated from Latin; and English and Old French, translated from Old French.
Includes bibliographical references and indexes.
Print version record.
Master record variable field(s) change: 082
Keywords: Christian heretics -- France -- Languedoc -- History; Languedoc (France) -- Church history -- To 1500.; Inquisition -- France -- Languedoc -- History; RELIGION -- History; Christian heretics; Inquisition; France -- Languedoc; To 1500; Electronic books; Church history; History